Impact of Drip Irrigation on the Income of Tomato Growers in Chhindwara (MP) - Ojha, Uttam; Singh, Kinjulck C; Khare, N K; Singh, Chandrajiit (Indian Journal of Extension Education, 2020)
Irrigation water is a limiting factor in selection of crops being cultivated. Traditional irrigation methods have low water use efficiency which allow a lot of water wastage as run off or seepage loss. A single irrigation in an acre of land costs about Rs. 1500/-. Therefore, it is important to know whether improved irrigation methods had any impact on income of vegetable growers. The comparative study attempts to explore difference in income of farmers who were using drip system of irrigation with those who were not using the same. Total 80 respondents were selected for study in which 40 tomato growers were drip users and 40 as non-drip users. Findings revealed that using drip irrigation system enhanced production as well as income of the tomato growers significantly in comparison to those who were not using drip irrigation system.